Changes of reaction time and blood lactate concentration of elite volleyball players during a game - Mroczek, D.; Kawczynski, A.; Chmura, J (Journal of Human Kinetics, 2011)
The purpose of this study was to investigate changes in reaction time of elite volleyball players during a game.Fourteen volleyball players participated in the study. Reaction time was measured using the Optojump system. In addition, blood lactate concentration was assessed to monitor physiological load during the game. All measurements were performed during a pre-game test and during sets 1, 2, 3 and 4. Reaction time during set 1 decreased significantly by 13,3 % compared with pre-game values, from 600 ms during the pre-game test to 520 ms during set 1 (p<0,05). Blood lactate concentration increased significantly during set 1, 2, 3 and 4 compared with pre-game conditions (p<0,05). Reaction time stays in the first phase of its changes pattern and elite volleyball players do not reach psychomotor fatigue threshold throughout the game.